Heterogeneous UV/Fenton-Like Degradation of Methyl Orange Using Iron Terephthalate MIL-53 Catalyst - Pham Dinh Du; Huynh Thanh Danh; Pham Ngoc Hoai; Nguyen Mau Thanh; Vo Thang Nguyen; Dinh Quang Khieu (Journal of Chemistry)
The synthesis and degradation of methyl orange (MO) in an ultraviolet-assisted heterogeneous Fenton-like process via the iron terephthalate (MIL-53) catalyst are demonstrated. MIL-53 material was characterized by means of X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), UV-Vis diffuse reflectance spectra (DR-UV-Vis), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and nitrogen adsorption/desorption isotherms. It was found that the obtained material shares an identical pattern of the MIL-53 structure with high crystallinity and also demonstrates the mesoporous phase with a pore diameter of around 4.2 nm and specific surface area, SBET, of 88.2 m2·g−1. MIL-53 with UV irradiation exhibits high catalytic activity for MO degradation by hydrogen peroxide. The factors affecting the efficiency of MO decomposition including pH of the solution, H2O2 concentration, catalyst dosage, initial MO concentration, and reaction temperature were addressed. The present catalyst is stable after four recycles with slight catalytic activity loss which makes it a potential candidate for environmental restoration.